2000
DOI: 10.1136/thorax.55.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitric oxide inhalation in chronic obstructive pulmonary disease

Abstract: Background-Inhalation of nitric oxide with oxygen could be a promising treatment in patients with chronic obstructive pulmonary disease (COPD) and pulmonary hypertension. However, the current methods of delivery of NO are cumbersome and unsuitable for long term use. The present study was undertaken to investigate the safety and eYcacy of a mixture of nitric oxide (NO) and oxygen administered via a nasal cannula for 24 hours in patients with oxygen dependent COPD. Methods-Twenty five parts per million (ppm) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Currently, prostacyclin derivatives, endothelin antagonists, and NO donors [30] have been effectively used in patients with primary pulmonary hypertension. We speculate that iNOS inhibitors may also be effective in the treatment of secondary pulmonary hypertension by reducing or reversing arterial wall and airway remodeling in COPD.…”
Section: Prostacyclin Synthasementioning
confidence: 99%
“…Currently, prostacyclin derivatives, endothelin antagonists, and NO donors [30] have been effectively used in patients with primary pulmonary hypertension. We speculate that iNOS inhibitors may also be effective in the treatment of secondary pulmonary hypertension by reducing or reversing arterial wall and airway remodeling in COPD.…”
Section: Prostacyclin Synthasementioning
confidence: 99%
“…Whereas the haemodynamic effects of combined NO and oxygen appear to be related to the NO dose, the amelioration in gas exchange seems to have a ceiling effect at a concentration of 5 ppm [110]. ASHUTOSH et al [111] showed that inhaled NO can be safely administered to COPD patients for 24 h. Nevertheless, the long-term administration of NO combined with oxygen is not easy and there is no evidence that it ameliorates pulmonary hypertension in COPD. …”
Section: Selective Pulmonary Vasodilatorsmentioning
confidence: 99%
“…86,87 Moreover, this combined use lowers PVR in such patients. Since there are inconsistent results with inhaled NO in patients with COPD, the therapeutic use of NO for PH in COPD patients needs further research.…”
Section: Inhalation Of Nitric Oxidementioning
confidence: 94%